Chronic hemodialysis patients at Fresenius Dialysis Centers from the Kuyavian-Pomeranian Voivodeship as primary health careand outpatient specialist care recipients– pilot study - Pluta, Agnieszka; Stróżecki, Paweł; Sulikowska, Beata; Marcinkowski, Wojciech (Nursing in the 21st Century, 2022)
CHRONIC HEMODIALYSIS PATIENTS AT FRESENIUS DIALYSIS CENTERS FROM THE KUYAVIAN-POMERANIAN VOIVODESHIP AS PRIMARY HEALTH CARE AND OUTPATIENT SPECIALIST CARE RECIPIENTS – PILOT STUDY Introduction. Depending on the stage and progression of the disease, patients with chronic kidney disease (Przewlekła Choroba Nerek ) – CKD receive care at various levels of the Polish healthcare system, including primary care (Podstawowa Opieka Zdrowotna) – PHC teams, specialist clinics (Ambulatoryjna Opieka Specjalistyczna) – AOS, hospitals, as well as dialysis and transplant centers. The study aimed at analyzing the use of PHC and AOS services by hemodialysis patients treated in Fresenius Dialysis Centers from Poland Material and methods. The study was based on a questionnaire survey and the Acceptance of Illness Scale questionnaire (Skala Akceptacji Choroby) – AIS. The total number of 159 patients participated in the study. The data was obtained from the Voivodeship Department of the National Health Fund on the use of PHC services in 2015, 2016 and 2017 by hemodialysis patients. Results. The mean age of the respondents was 67.1±13.1 years. Almost all hemodialysis patients (98.7%) required additional treatment for CKD comorbidities. Over the last year before the survey, 5.7% of the respondents used PHC nursing services and no woman used PHC midwifery services. Participation in “Leki 75+” PHC program was indicated by 37.3% of those eligible. In the said period, AOS services were used by 66.7% of the respondents, including a greater percentage of urban rather than rural inhabitants (71.1% vs 58%; p<0.05). Conclusions. Multiple morbidity and a high percentage of patients receiving AOS services in the analyzed period indicate the need to provide hemodialysis patients with coordinated care supervised by a dialysis center physician. Fulfilling PHC tasks by such physicians suggests the need to increase their numbers and to improve the financing of renal replacement therapy.